O52 Optical diagnosis of polyps <10mm and impact on surveillance interval (DISCARD3). (19th June 2022) - Ahmad, Ahmir; Moorghen, Morgan; Wilson, Ana; Stasinos, Ioannis; Haycock, Adam; Humphries, Adam; Monahan, Kevin; Suzuki, Noriko; Thomas-Gibson, Siwan; Vance, Margaret; Thiruvilangam, Kowshika; Dhillon, Angad; et al.
Abstract : Introduction: Optical diagnosis (OD) of diminutive (1–5mm) and small (6–9mm) polyps can be performed with advanced endoscopic imaging. When coupled with a 'resect and discard' strategy, for high confidence diagnoses, significant histopathology time and cost savings are possible. The threshold for implementation in practice is ≥90% OD-histology surveillance interval concordance. The aim of this study was to assess feasibility and implementation of ≤5mm and <10mm polyp OD in a bowel cancer screening setting. Methods: This prospective feasibility study involved 8 bowel cancer screening endoscopists completing a validated OD training module and performing procedures. All <10mm consecutive polyps were optically assessed using white-light and narrow-band images and given high or low confidence diagnoses until 120 high confidence ≤5mm polyp diagnoses had been made. All polyps had standard histology. Where high confidence OD did not match histology deeper histology levels were analysed. Histology-derived and OD-derived surveillance intervals were calculated using BSG, ESGE and US multi-society task force guidelines. Results: 565 patients were invited with 40 exclusions. Of the 525 patients included, 1771 polyps were identified of which 1752 were resected and retrieved. Of these, 1560 were <10mm (1329 ≤5mm and 231 6–9mm). Most <10mm polyps (74.9%, 1169/1560) were diagnosed with high confidence. There were no <10mm polyp cancers. High confidence OD was accurate in 81.5% of ≤5mm and 92.8% of 6–9mm polyps; overall accuracy (<10mm polyps) was 83.5%. The sensitivity for OD of a ≤5mm adenoma was 93.0% with a PPV of 90.8%. The sensitivity for OD of a ≤5mm serrated polyp was 80.2% with a PPV of 73.1%. Surveillance interval concordance, according to BSG, ESGE, and US multi-society task force guidelines, was assessed in 229 patients, who had only <10mm polyps and high confidence diagnoses (see table 1 ). Conclusions: On a per-polyp basis OD accuracy was greater for 6–9mm polyps compared to diminutive polyps and there were no <10mm polyp cancers. A 'resect and discard' strategy for high confidence ≤5mm polyp OD, in a group of bowel cancer screening colonoscopists, is feasible and safe with performance exceeding the 90% surveillance interval concordance (BSG, ESGE, US guidelines) required for implementation in clinical practice. For high confidence OD of polyps <10mm, performance exceeds the 90% surveillance interval concordance threshold for BSG and ESGE guidelines but not US guidelines.